Investment Decision with a General Equilibrium Mean-Variance Approach - Hamada, Robert S. (Quarterly Journal of Economics, 1971)
I. Introduction, 667. — II. Assumptions and a review of the market equilibrium model, 668. — III. Consumption and investment decisions jointly considered, 672. — IV. General equilibrium in a pure exchange economy, 676. — V. Productive activities by firms, 679. — VI. Conclusions, 682.